Use of Blast Furnace Slag and Steel in Asphalt Mixtures: Review (2018)
In the manufacture of asphalt mixtures, large quantities of natural stone aggregates are consumed, which has a negative impact on the environment. These aggregates can be partially or totally replaced by others that are disposed of in dumps and produced by steel companies, such as blast furnace slag (BFS) and steel (SS). These last two materials have chemical and physical properties that make them suitable for use in multiple applications such as road construction, maintenance and rehabilitation. The article presents a review of the state of knowledge of the use of BFS and SS in the production of asphalt mixtures, describes and defines both materials, presents the environmental problems, their toxicological risk of use, their chemical and physical properties, the advantages and limitations of use and the way they have been studied to be used as stone aggregates of asphalt mixtures. Based on the bibliographic review, the authors at the end of the article present some recommendations to continue the studies tending to substitute natural stone aggregates with BFS and SS in the manufacture of asphalt mixtures.